A framework for end-to-end approach to Systems Integration. (3rd December 2009) - Jain, Rashmi; Chandrasekaran, Anithashree; Erol, Ozgur
Systems Integration (SI) is an important element of systems engineering which involves the integration of hardware, software, products, services, business processes, and human. The existing standards, models, and guidelines of Systems Engineering and Software Engineering address SI issues partially and usually view SI from a perspective of integrating physical components. They lack a holistic end-to-end approach to SI. Due to the emerging Systems Engineering challenges and the increasing importance of SI, the need for a holistic approach to SI has become critical. A Systems Integration Framework (SIF) was developed that incorporates the relevant aspects of integration from a lifecycle perspective and sets a foundation to an end-to-end approach to SI.